Open Duodenal Switch for Treatment of Super Obesity—Surgical Technique. (March 2015) - Sundbom, M.
Background and Aims: Bariatric surgery is increasing worldwide; however, standard techniques, for example, gastric bypass, are often insufficient in super obese patients, body mass index > 50 kg/m 2 . Duodenal switch, a more powerful procedure, is often considered technically demanding and is, therefore, underutilized according to some authors. This might result in nonoptimal surgical care for super obese patients, not having the possibility to obtain massive weight loss. Material and Methods: In this report, we present our open duodenal switch technique, which we have found durable in an academic center performing 30–40 cases annually, parallel to other upper abdominal surgery. The present technique, performed through a short upper midline incision, consists of a gastric tube, a 1.5-m alimentary limb, and a 1-m common limb of the distal ileum. Conclusion: With correct follow-up to reduce the risk of malnutrition, we encourage the use of duodenal switch and see no rational surgical obstacles.